2017
DOI: 10.1016/j.cgh.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

HBV-Associated Acute Liver Failure After Immunosuppression and Risk of Death

Abstract: Background & Aims: Acute liver failure (ALF) due to hepatitis B virus (HBV) infection can occur after immunosuppressive treatment and be fatal, although it might be preventable. We aimed to characterize the causes, clinical course, and short-term outcomes of HBV-associated ALF after immune suppressive therapy, compared to patients with HBV-associated ALF without immunosuppression (controls). Methods: We performed a retrospective multi-center study of 156 consecutive patients diagnosed with HBV-associated ALF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Clinical data including organ support requirements (invasive mechanical ventilation, vasopressors and renal replacement therapy) and medical therapies (use of mannitol, hypertonic saline, barbiturates, hypothermia, sedatives, blood products and antibiotics) were recorded during the first 7 days post‐study enrolment or until discharge, death or transplant if before 7 days. Data retrieved on outcomes at 21 days post‐study enrolment included LT, TFS and overall survival …”
Section: Methodsmentioning
confidence: 99%
“…Clinical data including organ support requirements (invasive mechanical ventilation, vasopressors and renal replacement therapy) and medical therapies (use of mannitol, hypertonic saline, barbiturates, hypothermia, sedatives, blood products and antibiotics) were recorded during the first 7 days post‐study enrolment or until discharge, death or transplant if before 7 days. Data retrieved on outcomes at 21 days post‐study enrolment included LT, TFS and overall survival …”
Section: Methodsmentioning
confidence: 99%
“…Acute hepatitis B can progress to ALF in 1% to 4% of cases . In particular, ALF caused by HBV infection in an immunosuppressant state can be fatal . In one retrospective study, Karvellas et al noted that patients with HBV‐associated ALF receiving immunosuppression had a significantly higher mortality than those who did not receive immunosuppression.…”
Section: Acute Hepatitis B and Liver Failurementioning
confidence: 99%
“…In particular, ALF caused by HBV infection in an immunosuppressant state can be fatal . In one retrospective study, Karvellas et al noted that patients with HBV‐associated ALF receiving immunosuppression had a significantly higher mortality than those who did not receive immunosuppression. They recommend that this population of patients be screened for HBV infection and be treated accordingly when infection is present .…”
Section: Acute Hepatitis B and Liver Failurementioning
confidence: 99%
See 1 more Smart Citation
“…There is high inter‐individual variability in the clinical presentation of HBV infection, which ranges from self‐limited to fulminant acute disease and from mild chronic hepatitis to liver cirrhosis and hepatocellular carcinoma . Differences in viral or environmental factors only explain a fraction of this variability . Previous studies have identified some human genetic factors that play a modulating role in the clinical course `of HBV infection .…”
Section: Introductionmentioning
confidence: 99%